Synergistic Impact of Brand Experience, Trust, and Brand Ambassadors on Purchasing Decisions - Siswati, Endang; Rapitasari, Diana (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research is a quantitative study aimed at testing and analyzing whether brand experience, brand trust, and brand ambassador influence consumer purchase decisions of products. The sample in this study consisted of 100 people, and the respondents were domestic consumers of Artistica Jewelry. The research results show that brand ambassador, brand trust, and brand experience have a significant influence on purchasing decisions. Among these three variables, brand trust is the dominant variable affecting purchasing decisions at Artistica Jewelry. The company must maintain consumer trust in product quality and service, as well as brand consistency, in the hope of generating word-of-mouth sales. Consumer trust develops because of the belief that the company will act in accordance with their needs and expectations.